STRATEGI PEMERINTAH DALAM MEWUJUDKAN LAMPUNG THE TREASURE OF SUMATRA CITY BRANDING : (Studi Pada Dinas Pariwisata dan Ekonomi Kreatif Provinsi Lampung) - Amelinda, Rizky; Pramazuly, Ayu Nadia; Mosshananza, Hinfa (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2024)
The problem in this study is that the tourism and culture sectors of Lampung Province have not received enough attention, and tourism promotion has not been effective. The strategy implemented has not been successful with local governments. This can be seen from the fact that both natural tourism and cultural tourism have tourism potential that has not been utilized optimally. In fact, if utilized properly, the tourism industry can provide income for the community and local government. The purpose of this study is to determine the government strategy for realizing Lampung The Treasure of Sumatra City Branding. The research method used is qualitative descriptive research, which is an analysis based on data obtained through interviews with informants, observation, and documentation. The results of this study are (1) to produce accurate information about the government's strategy in realizing Lampung Treasure of Sumatra City Branding, (2) to produce 13 government strategies for realizing Lampung Treasure of Sumatra City Branding using SWOT analysis. Suggestions for the Government: The government should socialize more about slogans Lampung Treasure of Sumatra City Branding to society at large through the digital world, The Regional Government should continue to increase its attention to existing tourism to ensure that it is managed properly, and the Regional Government should continue to develop the existing tourism potential in Lampung Province so that it can become a leading tourism destination in the future. Keywords: Strategy; Government; Tourism; City Branding